JOURNAL WRITING ASSISTANCE AS A MANIFESTATION OF AUTHENTIC TEACHERS IN THE INDEPENDENT LEARNING CURRICULUM AT THE SD/MI LEVEL - Siregar, Nasyariah; Saputri, Vioni; Pambudi, Yudha Rello; Lestari, Febria; Nisa, Ikhfah Chairun (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This article discusses the mentoring process of reflective journal writing. The purpose of the article is to describe the application of reflective journal writing in learning. The method used is the Participatory Action Research (PAR) method. The description of the results and discussion shows that the mentoring has been running and the teacher has applied three components in reflective journal writing, 1) the description component, the teacher documents the experience, expresses feelings and thoughts, and describes the cases encountered, 2) the evaluation component, the teacher reassesses the learning process carried out, 3) the reflection component, the teacher finds a pattern of maximizing time, material adjustment, media, And the method also needs further improvement. This has an effect, because realizing authentic teachers, of course, must further examine the learning carried out has reached standardization according to the teaching modules applied.